Das Paradoxon des Eskapismus beim tschechisch-deutschen Schriftsteller Jaroslav Rudiš - Pytlík, Petr (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
This article examines the motif of escapism in selected novels by Jaroslav Rudiš (Winterbergs letzte Reise, Grandhotel, Der Himmel unter Berlin and Nationalstraße) in light of Theodor W. Adorno’s aesthetic theory. The starting point is the observation that while Rudiš’s protagonists flee from a reality they perceive as oppressive, this act of escape paradoxically leads to an awareness of reality itself. The so-called “paradox of escapism” – derived from Adorno’s Negative Dialectics and his conception of art as a form of knowledge – serves as an interpretive framework. The analysis shows that escapism is effective on several levels in Rudiš’s work: as an experience of the reader, as a narrative strategy, and as an existential stance of the characters. While Der Himmel unter Berlin exposes escapism as an illusory counter-world, in Grandhotel it appears as a therapeutic process of self-discovery. In Národní třída, escape transforms into aggressive self-mythologizing, and in Winterbergs letzte Reise, escapism finally becomes an instrument of knowledge that makes visible the historical and personal guilt of Central Europe. This essay thus understands Rudiš’s work as an attempt to renegotiate the fragile identity of Central Europe through aesthetic escapism. Escapism, in this context, proves not to be the opposite of reality, but rather its necessary precondition: only the detour via the imaginary enables the recognition of the real.